An An In-Depth Examination of the Blended Teaching Mode: Integrating Online and Offline Approaches in Automotive Education - Yang Jiyong; Jesse Balinas (International Journal of Education and Humanities, 2026)
This study investigates the implementation and acceptance of blended teaching methods in automotive education at Liaocheng Vocational and Technical College. Blended teaching, which combines traditional face-to-face instruction with online learning activities. Using the quantitative approach. findings reveal that while teachers demonstrate strong competencies in technology integration and pedagogical adaptation, there is a need for further improvement in optimizing interactive learning and troubleshooting technical issues. Professional development participation is high, but a proactive engagement in innovative methodologies is required. Students show a high level of acceptance towards the blended teaching mode, with strong engagement in online materials and a positive response to peer collaboration. However, the findings also highlight a need for increased digital access and strategies to improve student self-discipline. No significant differences were found across age groups, gender, or year levels regarding feedback, online engagement, and peer collaboration, suggesting that other factors influence learning experiences. Additionally, gender disparities were noted in professional development participation and the overall implementation of blended teaching, with male teachers reporting higher engagement. The study concludes with practical recommendations for optimizing blended teaching strategies, enhancing teacher professional development, and improving student learning experiences through targeted interventions